In patient satisfaction survey- how does it help our health care delivery system (the patient, the health care giver and the organization)? - Shah, Priti Prasad (International Surgery Journal, 2017)
Background: Patient satisfaction is a mean of measuring the effectiveness of health care delivery. It can suggest proportion to the problem areas and a reference point to take management decisions. It can serve as a mean of holding physician accountable. Patient satisfaction data can be used to document health care quality for accrediting organizations and consumer groups. They can also measure specific initiative or changes in service delivery. They can increase loyalty of patients by demonstrating you care their perceptions and looking for ways to improve. The purpose of our study is to carry out evaluation of hospital services by getting a patient satisfaction survey. Main aim is to identify potential problems in the services. Methods: A hospital based inpatient satisfaction survey study done on 200 patients. A Predesigned structured questionnaire was based on relevance of questions to healthcare services on various aspects of inpatient care. The interviewer based questionnaires were filled after obtaining verbal informed consent from all subjects. 200 valid responses were analyzed using MS office excel. Data analysis of study is done using the SPSS (Statistical Package for the Social Science) Version 17 for window. Results: Results of our study is very positive and suggest that patients were satisfied with the attitude of doctors, nurses and paramedical staff and it was appreciated. As in D Y Patil Medical College and Hospital most facilities are free for the patients, so we got better feedback for the facilities and satisfaction for this study. Satisfied patients are more likely to continue using the health care services and maintain their relationship with specific health care providers. Conclusions: Patient satisfaction survey can be a driving force for changes in health care delivery with institutions and individuals. These initiatives can promote improvement in practice and also respond to patient expressed needs.